Dampak Pandemi Covid-19 yang Membawa Pengaruh Individualistik dan Implikasinya Bagi Orang Percaya Masa Kini - Baskoro, Paulus Kunto (Sekolah Tinggi Teologi Kanaan Nusantara, 2021)
The Covid-19 pandemic has brought about extraordinary changes. No one in this world thought that the Covid-19 pandemic would occur. The occurrence of Covid-19 has brought about an essential and fundamental change in human life. Dratic changes occurred in the health sector, then had a strong impact on education, business economics and even families. The general impact cannot be denied to be negative. And the biggest effect of Covid-19 is the individualistic behavior of people during the Covid-19 pandemic.People tend to focus on themselves because Covid-19 has made the distance even further in terms, especially social relationships. Even the biggest reason for living individually is so as not to catch the Covid-19 virus. This is completely irrelevant to the most essential human needs, namely to socialize and humans were created by God as social beings. And from the point of view of the truth God’s Word is very inaccurate. This writing uses the method of descriptive literature. The goal is that through writing, First, to clarify the impact of Covid-19 which has an individualistic influence on everyone; Second, to find put the individualistic influence on everyone during the Covid-19 pandemic from the results of the writing; Third, providing theological implications of the attitude of believers to always live as a blessing during the Covid 19 pandemic.AbstrakPandemi Covid-19 membawa perubahan yang luar biasa. Tidak ada satu orangpun di dunia ini yang menyangka pandemi Covid-19 terjadi. Terjadinya Covid-19 membawa dampak perubahan secara esensi serta mendasar dalam kehidupan umat manusia. Perubahan dratis terjadi dalam bidang kesehatan, kemudian berimbas kuat di bidang pendidikan, bidang ekonomi bisnis bahkan keluarga. Dampak secara umum tidak bisa dipungkiri terjadi secara negatif. Dan efek terbesar dari Covid-19 adalah perilaku individualistik orang di masa pandemi Covid-19. Orang cenderung fokus kepada diri sendiri karena Covid-19 membuat jarak makin jauh dalam secara sisi, khususnya hubungan sosial. Bahkan alasan terbesar untuk hidup secara individualistik adalah supaya tidak tertular virus Covid-19. Hal ini sangat tidak relevan dengan kebutuhan manusia yang paling esensi, yaitu bersosialisasi dan manusia diciptakan Tuhan sebagai makhluk sosial. Dan dipandang dari sisi kebenaran Firman Tuhan sangat tidak tepat. Penulisan ini menggunakan metode deskritif literatur. Tujuannya supaya lewat penulisan yaitu Pertama, untuk mengklarifikasi dampak Covid-19 yang membawa pengaruh individualistis kepada setiap orang; Kedua, untuk mengetahui pengaruh individualistis pada setiap orang di masa pandemi Covid-19 dari hasil penulisan; Ketiga, memberikan implikasi teologis sikap orang percaya untuk selalu hidup menjadi berkat dalam masa pandemic Covid 19.